Perceived digital health information support and self-rated health among Chinese adults: physical activity mediation and chronic health condition moderation - Xiaochu Yang; Xiang Fu; Zexin Wu; Linying Xiao; Ming Luo (Frontiers in Public Health, 2026)
Background Digital health resources provide new opportunities for health information seeking, decision-making, and self-management. Yet residents differ in how they understand, evaluate, and use online health information. This study focuses on perceived digital health information support, namely the perceived usefulness of internet-based information for medical understanding and health-related decision support. Evidence remains limited on how this perceived support relates to self-rated health through physical activity and whether this association differs by chronic health needs and population characteristics. Objective This study examined the association between perceived digital health information support and self-rated health from a health equity perspective, tested the mediating role of physical activity, and examined moderation by chronic health conditions and subgroup-specific patterns. Methods This cross-sectional study used data from the Chinese General Social Survey 2021. The analytic sample consisted of 2,690 respondents from the CGSS 2021 health module. Statistical analyses were performed using Stata 18.0. Multivariable linear regression used community-clustered robust standard errors and province fixed effects. Bootstrap mediation analysis used 5,000 resamples. A second-stage moderated mediation model tested chronic health conditions. Weighted models, complete-case sensitivity analyses, formal bootstrap contrasts for subgroup differences, and ordered logit models including the physical activity by chronic condition interaction were used as robustness checks. Results Perceived digital health information support was positively associated with self-rated health and physical activity. Physical activity represented a statistically significant indirect component of the observed association between perceived support and self-rated health; this indirect component accounted for 9.35% of the observed total association. Chronic health conditions strengthened the observed association between physical activity and self-rated health. Formal bootstrap contrasts indicated that the indirect association differed significantly by age, whereas contrasts by sex, marital status, and socioeconomic status were not statistically significant. Conclusions Perceived digital health information support was associated with self-rated health among Chinese adults. Physical activity was one behavioral pathway statistically linking perceived online health information support to health evaluation, especially among adults with continuing health needs. Digital health interventions should combine accessible information support with feasible physical activity opportunities and offline behavioral support to avoid widening digital health inequities.